Clinicopathological study of testicular tumors: an experience in a tertiary care hospital in Kashmir valley, Jammu and Kashmir, India - Beigh, Ambreen; Junaid, Sheikh; Beg, Arshi; Farooq, Summyia; Wani, Lateef Ahmed; Manzoor, Farzana (International Journal of Research in Medical Sciences, 2017)
Background: Testicular and paratesticular neoplasia are rare type of tumors affecting adolescents and young adults in India, as observed by paucity of published data. This study was undertaken to analyze the patterns of testicular tumors at a tertiary level hospital in Kashmir valley, Jammu and Kashmir, India highlighting the patient’s demography, clinical presentation, diagnostic evaluation and pathological finding. Methods: This 5-year (retrospective and prospective) study was performed in the Department of Pathology, Government Medical College Srinagar, Jammu and Kashmir, India from January 2012 to December 2016. For the retrospective study, all cases of testicular tumors, their histopathological reports and required clinical details were searched from records maintained in the Department of Pathology, GMC Srinagar, Jammu and Kashmir, India. For the prospective study, the orchiedectomy specimens received in our department were subjected to routine histopathological processing followed by a detailed gross and microscopic examination. Tumour typing and subtyping was done according to WHO classification (2004). Results: A total of 37 cases of testicular and paratesticular neoplasia were included in present study with a mean age of 35.1 years. Out of these 37 cases, 31 (83.78%) were malignant and 6 cases (16.22%) were benign. Right testis was affected in 70.3% of cases. The most common clinical presentation was scrotal swelling. Germ cell tumor was the most common type accounting for 89.2% of tumors followed by lymphomas (8.1%). Conclusions:It is concluded that despite new techniques in imaging and tumor marker assay, the diagnosis of testicular tumors is dependent upon histopathological examination. The present study fairly provides an insight into the clinical presentations, prevalence and patterns of testicular tumors.